The Dirichlet Problem for elliptic equations in unbounded domains of the plane - Paola Cavaliere; Maria Transirico (Journal of Function Spaces and Applications)
In this paper we prove a uniqueness and existence theorem for the Dirichlet problem in W2,p for second order linear elliptic equations in unbounded domains of the plane. Here the leading coefficients are locally of class VMO and satisfy a suitable condition at infinity.